Marketing Mix 7P and Repeat Purchase Behavior in Café Business: Bauran Pemasaran 7P dan Perilaku Pembelian Berulang dalam Bisnis Kafe - Audiansyah Agni Nirvana; Moch. Tutuk Safirin (Academia Open, 2025)
General Background: The food and beverage industry faces intense competition, prompting businesses to apply strategic marketing to reach and retain consumers. Specific Background: A café business in Surabaya is used as a case to assess how marketing strategies affect customer behavior in a highly competitive market. Knowledge Gap: There is limited empirical analysis on how the individual components of the Marketing Mix 7P influence both purchasing and repurchasing decisions within local food service settings. Aims: This study aims to examine the role of the Marketing Mix 7P (Product, Price, Place, Promotion, People, Process, and Physical Evidence) in shaping purchasing and repurchasing decisions using the Structural Equation Modeling (SEM) approach with AMOS software. Results: Data collected from 120 respondents through an online questionnaire show that Product and Place significantly influence purchasing decisions. People, Process, and Physical Evidence do not show significant effects, while Price and Promotion were removed due to multicollinearity. Furthermore, purchasing decisions are found to significantly affect repurchase behavior, while none of the marketing mix variables directly influence repeat purchases. Novelty: This study presents empirical findings from a local café context using SEM to uncover which marketing factors matter most in influencing consumer behavior. Implications: Results suggest focusing marketing strategies on product quality and location to encourage initial purchase, which in turn supports repeat purchase behavior. Highlights: Product and Place significantly affect purchasing decisions. Purchasing decisions drive repeat purchase behavior. Price and Promotion excluded due to multicollinearity issues. Keywords: Marketing Mix, SEM, Consumer Decision, Repurchase, Food Service